STUDY OF THE RELEVANCE OF THE SOCIO-ECONOMIC COMPONENT OF THE GOALS OF ACHIEVING SUSTAINABLE DEVELOPMENT OF AGRARIAN BUSINESS AND FOOD SECURITY OF THE REGION - Bashlai, Serhii (European Science, 2024)
The scientific work is devoted to the research and development of a strategy for sustainable development and regional food security. The goal was the study of approaches to solving the tasks of ensuring food security in the conditions of military operatio